BOOSTING STUDENTS’ SPEAKING SKILL IN THE PANDEMIC ERA USING PROBLEM BASED LEARNING VIDEO - I Gusti Ayu Dwi Pradnyandari Pinatih; Putu Kerti Nitiasih; luh Gd Rahayu Budiarta; Ni Luh Putu Era Adnyayanti (PROJECT (Professional Journal of English Education), 2021)
Speaking is one of four skills which quite difficult to teach in the pandemic era. The implementation of a learning video in speaking class become one solution that can used to make teacher easier to tech speaking to students. The study aimed to determine the video used as a learning media in boosting students’ speaking skills in the pandemic era. This research used quasi experimental design which applied one pre-test and post-test group. The group got two different treatments at once. The subject was students in the fifth-grade elementary school. To collect the data, the instruments used included video, pre-test, and post-test. All of the data which obtained were calculated using the SPSS 20 version. Data statistics showed that the mean score were improved from pre-test (63.23) to the post-test (84.52). After the normality and homogeneity test, the data obtained were categorized as a normal and homogeny. In addition, according to the data analysis, it found that the null hypothesis was rejected which mean that the used of educational learning video was very effective for boosting and improving students’ speaking skills. Keywords:  Video, Speaking Skill, PBL